“The Gay Factor” – Exploring the Gay/Straight Wage Gap in Men - Thien Mai (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
Is there a wage penalty for being gay? Previous research has indicated a sizable wage gap between gay and straight men of up to 25%. At the same time, national polling indicates increasing acceptance of gay marriage and gay relationships in general. Using the most recent data available (American Community Survey, 2012), I find a gay premium of ~6%, a number which is robust across a number of sample limitations. This premium may be partially related to urban residence which is unobserved in the public use samples of the ACS.